Hepatitis C Virus Core Antigen Test: an HCV RNA screening alternative in end-stage renal disease and hemodialysis? - Alves,Rita V (2019)
Introduction and Aim:Hepatitis C virus screening using anti-HCV antibody is recommended for end-stage renal disease and chronic hemodialysis patients. Since the anti-HCV antibody test is not able to differentiate a concurrent infection from a resolved past one, a more reliable and cost-effective screening test is needed. Materials and Methods: Prospective study of end-stage renal disease and chronic hemodialysis patients from a hospital unit who were screened by anti-HCV antibody and total ARCHITECT® HCV antigen assay. Results: Cohen's κ test was run to determine if there was agreement between HCV Ribonucleic Acid and HCV core antigen assays on 7 individuals with positive anti-HCV antibody. The two tests had a perfect measurement agreement. Conclusions: HCV core antigen testing could be used as a sensitive method for HCV infection screening in this group of patients based on its accuracy, simplicity and low expense